Extra-Adrenal Retroperitoneal Myelolipoma Resected by Laparoscopy in an Asymptomatic Patient - Gabriel Ambrogi; Maria Madureira Murta; André Silva Guimarães Moeda; Ramon Brandão Barbosa; Israel Rodrigues da Silva; Ana Beatriz Tabosa Negrão Xavier; Matheus Vieira dos Santos; Lucas Martinucci de Oliveira; Bernardo Luiz Campanário Precht; Renato Panhoca; Luis Augusto Seabra Rios (Case Reports in Surgery)
Myelolipomas are rare benign neoplasms that commonly develop in the adrenal glands. Less frequently, they can affect other organs such as the liver, stomach, liver, lung, and retroperitoneum. It affects more women, with an average age of around 61 years. Histologically, they are composed of mature adipose tissue and hematopoietic cells. With the evolution of immunohistochemistry, there are characteristics that can differentiate from malignant tumors such as liposarcomas. Its treatment remains based on surgical resection and long-term outpatient follow-up.